Screening and transcriptomic analysis of anti-Sporothrix globosa targeting AbaA - Wang, Ying; Wu, Xiaoyan; Fan, Xiyuan; Han, Chanxu; Zheng, Fangliang; Zhang, Zhenying (Frontiers in Microbiology, 2025)
IntroductionSporotrichosis is a fungal disease caused by a complex of Sporothrix schenckii, leading to chronic infections of the epidermis and subcutaneous tissue in both humans and animals.MethodsThrough virtual screening targeting the key gene abaA to screen out the small-molecule drugs to treat Sporotrichosis. To further validate the antifungal activity of small-molecule drugs, growth curves, minimum bactericidal concentration (MBC), and minimum inhibitory concentration (MIC) for Sporothrix globosa (S. globosa) and Sporothrix schenckii (S. schenckii) were measured. In addition, we have done animal experiments to explore the function of the drugs. At the same time, qRT-PCR and transcriptome were used to verify the important role of abaA gene in Sporothrix.ResultsAzelastine and Mefloquine effectively inhibit S. globosa and S. schenckii. MBC, and MIC for S. globosa and S. schenckii confirmed that both Azelastine and Mefloquine inhibited the growth of S. globosa and S. schenckii. Additionally, animal experiments demonstrated that Azelastine and Mefloquine reduced skin lesions in mice; post-treatment observations revealed improvements in inflammatory infiltration and granuloma formation. Through transcriptome analysis and qRT-PCR for validation, our findings demonstrate that the abaA gene plays a crucial role in regulating the attachment of the Sporothrix cell wall to the host matrix and in melanin regulation. Notably, when the abaA gene was inhibited, there was a marked increase in the expression of repair genes. These results emphasize the significance of the abaA gene in the biology of Sporothrix.DiscussionTwo small-molecule drugs exhibit the ability to inhibit Sporothrix and treat sporotrichosis both in vitro and in murine models, suggesting their potential for development as therapeutic agents for sporotrichosis. And qRT-PCR and transcriptome results underscore the significance of the abaA gene in Sporothrix. Our results lay the foundation for the search for new treatments for other mycosis.